Renata Tomaszewska-Lipiec (ed.) / Professional education in the context of knowledge based economy. Bydgoszcz 2013 (Przegląd Pedagogiczny, 2015)
Recenzja publikacji: Renata Tomaszewska-Lipiec (ed.), Professional education in the context of knowledge based economy.